2017
DOI: 10.12890/2016_000516
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Lysis Syndrome and Partial Remission Occurring After Administration of a Test Dose of Obinutuzumab

Abstract: Chronic lymphocytic leukaemia (CLL) is one of the most common haematological malignancies worldwide, with an increasing prevalence in the elderly population. Obinutuzumab is a type II anti-CD20 monoclonal antibody which showed superiority over rituximab in combination chemotherapy with chlorambucil for the treatment of CLL in the CLL11 trial (NCT01010061) and is becoming part of standard first line treatment for CLL in the elderly based on its potent efficacy and benign safety profile. We report the case of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…TLS was reported following treatment with elotuzumab, however the picture in this case was complicated by pre‐treatment with lenalidomide and concomitant medications [ 8 ]. In a case of chronic lymphocytic leukaemia (CLL), a single test dose of obinutuzumab led to TLS and rapid tumour reduction [ 9 ].…”
mentioning
confidence: 99%
“…TLS was reported following treatment with elotuzumab, however the picture in this case was complicated by pre‐treatment with lenalidomide and concomitant medications [ 8 ]. In a case of chronic lymphocytic leukaemia (CLL), a single test dose of obinutuzumab led to TLS and rapid tumour reduction [ 9 ].…”
mentioning
confidence: 99%
“…However, Giordano et al, have been reported that in an octogenarian, the only clinical symptoms of generalized tetanus, dysphagia and tremor 7 . It has been reported that isolated bulbar symptoms, as dysphagia, in elderly, may be included in the differential diagnosis 8 . To this regard, the European Society for swallowing disorders-European Union Geriatric Medicine Society describe that dysphagia can cause severe complications such as malnutrition, dehydration, respiratory infections, aspiration/pneumonia and increased readmissions, institutionalization and mortality.…”
Section: Introductionmentioning
confidence: 99%